Helmut Lachenmann: Schwankungen am Rand - Lachenmann, Helmut 1935-; Eötvös, Péter 1944-; Ensemble Modern (München ECM Records, 2002)
The New York Times recently asked the question "Who is the most influential European composer of the moment?" and answered that no name "comes to mind more immediately than that of Helmut Lachenmann: The best of his work takes you by the hand and will not let you go until it has shown you things you could not have suspected." The first New Series disc by the great German composer/inventor resounds with startling sound-events, realized brilliantly - and dramatically - by the Ensemble Modern and the Ensemble Modern Orchestra, under the inspired direction of Peter Eötvös. These compositions from 1974/75, 1983/84 and 1992 represent key moments in Lachenmann's restless voyage of sound-discovery